Functionalization of carbon catalyst derived from corncob residue via hydrothermal technique for esterification of palm fatty acid distillate - Ibrahim, Siti Fadhilah (2021)
Biodiesel as an energy resource was recognized as a potential low carbon alternative to overcome the declining fossil fuel reserves. However, the higher cost production of biodiesel become the main problem. In this work, low-cost biodiesel was successfully produced through esterification of palm fatty acid distillate (PFAD) over heterogeneous solid acid catalyst derived from corncob residue. This catalyst was synthesized via hydrothermal carbonization followed by chemical activation using concentrated sulfuric acid and known as hydrothermal carbon-sulfonated (HTC-S). The prepared catalysts were characterized by using X-Ray Diffraction (XRD), Brunauer - Emmett –Teller (BET) Surface Area Measurement, Fourier Transform Infrared (FT-IR) Spectroscopy, Temperature Programmed Desorption of Ammonia (NH3-TPD) and Field-Emission Scanning Electron Microscopy (FESEM) analysis. The carbonization process leads to the cyclic carbon rearrangement by removing hydroxyl molecules and the sulfonation treatment on the carbon structure increase the acid properties with the total acid density of 13.00 mmol/g and surface area of 8.40 ± 0.15 m2/g. The esterification of PFAD over HTC-S catalyst was optimized via the one-variable-at-a-time technique, and 92% free fatty acid (FFA) conversion with a biodiesel yield of 85% were achieved at condition of 2 h reaction time, 70 °C reaction temperature, 3 wt.% catalyst loading, and 15:1 methanol-to-oil molar ratio. Various of catalyst regeneration techniques were analyzed and sulfuric acid treatment was found to be the most effective approach for restoring the active sites for spent HTC-S catalyst. The HTC-S catalyst regenerated via sulfuric acid treatment is capable to convert PFAD to biodiesel with FFA conversion until five consecutive cycles. In this work, the synthesized PFAD-derived biodiesel has complied with the international biodiesel standard ASTM D6751.